Impact of proteases on iron uptake of Pseudomonas aeruginosa pyoverdin from transferrin and lactoferrin. - Döring, G (1988)
The Pseudomonas aeruginosa siderophore pyoverdin was unable to acquire iron from human transferrin or lactoferrin at physiological pH. However, in the presence of P. aeruginosa elastase, rapid iron release and pyoverdin iron uptake from transferrin but not from lactoferrin were detected. Neither P. aeruginosa alkaline protease nor elastase from polymorphonuclear leukocytes revealed this effect.